Lego-based Game as a Way to Improve Student’s Physics Education - Emannuel Saptaputra; Bayu Dirgantoro; Sebastian Andrew (Journal of Games, Game Art, and Gamification, 2023)
During the pandemic, most students are having difficulties interacting with one another. Despite being under quarantine for more than two years due to the global pandemic, remote learning has not been an efficient way to continue education. Most of them are struggling with specific subjects during online classes. Furthermore, students have trouble in all their classes, and Physics is the most difficult subject, according to news reports and statistics on education. The results of all the studies and interviews with the qualitative respondents indicate that educational games might improve students' academic performance. As a result, puzzle-game physics was developed to help students.